Nature and pattern of primary teeth extractions in a tertiary care hospital setting in South India - Shini Susan Samuel; Daniel Sathiya Sundaram Selvaraj; Jagadish Ebenezer; Grace Rebekah; Santosh Koshy (Indian Journal of Dental Research, 2018)
Background: Many studies have been carried out on the prevalence of dental diseases in children although not much information is available regarding its outcome among Indian children. Aim: The aim of the present study was to analyze the type of primary tooth extracted and the reasons for the extraction among children attending a tertiary care hospital in the Southern part of India. Materials and Methods: The dental records of pediatric patients who had visited the dental clinic of a tertiary care hospital located in Tamil Nadu, South India from December 2013 to November 2016 were reviewed. Patients who underwent extraction of at least one primary tooth under local or general anesthesia were included in the study. Results: A total of 943 primary teeth were extracted from 447 patients over 3 years. The most commonly extracted tooth type was the first primary molar followed by the primary central incisor. Grouping by age, the most frequently extracted tooth type between 2 and 5 years was the primary central incisor, the first primary molar among the 6–9-year-old and the second primary molar among 10–15-year-old. The majority of primary teeth extractions were performed in the age group of 6–9 years. No significant gender differences were noted. The most common reason for extraction of primary teeth in children was dental caries. Conclusions: This study demonstrates a high prevalence of untimely primary teeth extractions in young children and dental caries continues to be the leading cause. It clearly reflects on the lack of infant oral health care, the inadequacy of awareness and underutilization of oral health services among children in India.